Study on Outcome of Phacoemulsification Cataract Surgery with Clear Corneal Steep Axis Incision - Raihan, Mohammad Hussain; Kabir, Farah Hossaini; Khan, Kamrul Hasan; Kajmina, Natasha; Hasan, A K M Rashedul; Hasan, Mohammad Mahbubul (Community Based Medical Journal, 2024)
A prospective, observational study was conducted in the Department of Ophthalmology, Combined Military Hospital (CMH), Dhaka, Bangladesh, from April to October of 2019, to observe the outcome and determine the amount of surgically induced astigmatism in phacoemulsification cataract surgery done with clear corneal incision. A total of 60 patients were included in this study. Cataract extraction was done in all the patients by phacoemulsification through clear corneal incision with foldable intraocular lens implantation. All the surgeries were done with INTREPID Micro-Coaxial system using the INFINITI Vision system by the same surgeon under local anaesthesia. The patients were followed up on 1st, 7th, and 30th POD. The parameters recorded were uncorrected visual acuity, best-corrected visual acuity, slit lamp examination, and keratometry. Due to clear corneal incision on steep axis, the steep meridian became flat, from 44.329±1.473D (diopter) (as found in pre-operative keratometry) to 43.971±1.431D (on the 30th post-operative day). On the other hand, the flat meridian became steeper from 43.225±1.471D (pre-operative) to 43.225±1.501D (on the 30th day). At preoperative examination and 30th day follow-up visit, astigmatism was determined as 1.10±0.319 and 0.583±0.413 respectively. The change of astigmatism was statistically significant (P<0.05). CBMJ 2024 January: vol. 13 no. 01 P: 41-45